Perceived financial decline related to breast reconstruction following mastectomy in a diverse population‐based cohort. Issue 6 (30th November 2021) - Berlin, Nicholas L.; Abrahamse, Paul; Momoh, Adeyiza O.; Katz, Steven J.; Jagsi, Reshma; Hamilton, Ann S.; Ward, Kevin C.; Hawley, Sarah T.
Abstract : Background: Despite mandated insurance coverage for breast reconstruction following mastectomy, health care costs are increasingly passed on to women through cost‐sharing arrangements and high‐deductible health plans. In this population‐based study, the authors assessed perceived financial and employment declines related to breast reconstruction following mastectomy. Methods: Women with early‐stage breast cancer (stages 0‐II) diagnosed between July 2013 and May 2015 who underwent mastectomy were identified through the Surveillance, Epidemiology, and End Results registries of Georgia and Los Angeles and were surveyed. Primary outcome measures included patients' appraisal of their financial and employment status after cancer treatment. Multivariable models evaluated the association between breast reconstruction and primary outcomes. Results: Among 883 patients with breast cancer who underwent mastectomy, 44.2% did not undergo breast reconstruction, and 55.8% underwent reconstruction. Overall, 21.9% of the cohort reported being worse off financially since their diagnosis (25.8% with reconstruction vs 16.6% without reconstruction; P  = .002). Women who underwent reconstruction reported higher out‐of‐pocket medical expenses (32.1% vs 15.6% with expenses greater than $5000; P  < .001). Reconstruction was independently associated with a perceived decline in financial status (odds ratio, 1.92; 95% confidence interval, 1.15‐3.22; P  = .013). Among women who were employed at the time of their diagnosis, there was no association between reconstruction and a perceived decline in employment status ( P  = .927). Conclusions: In this diverse cohort of women who underwent mastectomy, those who elected to undergo reconstruction experienced higher out‐of‐pocket medical expenses and self‐reported financial decline. Patients, providers, and policymakers should be aware of the potential financial implications related to reconstruction despite mandatory insurance coverage. Abstract : Among 883 patients with breast cancer who underwent mastectomy, women who underwent reconstruction reported higher out‐of‐pocket medical expenses and were independently more likely to report a perceived decline in their financial status. Patients, providers, and policymakers should be aware of the potential financial implications related to reconstruction despite mandatory insurance coverage.